2010
DOI: 10.4236/engineering.2010.28074
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Generation of Zn-Chitosan Composite Coating on Mild Steel and its Corrosion Studies

Abstract: A Zinc-Chitosan composite coating was generated on mild steel from zinc sulphate-sodium chloride electrolyte by electrodeposition. The electrolyte constituents were optimized for good composite coating. The corrosion resistance behavior of the composite was examined by weight loss, polarization and impedance methods using 3.5 wt% NaCl neutral solution as medium. Separate polarization profiles were recorded for composite coating and compared with zinc coated sample. SEM images of coatings were recorded for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The addition of extract provides protection layer in the surface, and the protection surface reach almost 100% of surface area for extract concentration of 2.5%. It is observed that the protective surface layer contains oxygen and other functional groups, as also observed by other researcher [12]. This is also consistent with the protection mechanisms that occur in the case using other natural ingredients [13] where the compound contains an atom that has a lone pair.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The addition of extract provides protection layer in the surface, and the protection surface reach almost 100% of surface area for extract concentration of 2.5%. It is observed that the protective surface layer contains oxygen and other functional groups, as also observed by other researcher [12]. This is also consistent with the protection mechanisms that occur in the case using other natural ingredients [13] where the compound contains an atom that has a lone pair.…”
Section: Resultssupporting
confidence: 88%
“…It is needed around 2.5%v of TCPE to cover the entire surface. This indicates that the inhibitor is able to form a surface layer which can block the attack of such aggressive acid, as also observed by other researcher [12]. However, the layer is not observed clearly in optical micrographs.…”
Section: Resultssupporting
confidence: 62%
“…A significant increase in the charge transfer resistance was observed for coated mild steel surfaces. The electro-deposition of Zn-chitosan composite coating on mild steel and its corrosion studies has been reported in 3.5% NaCl [47], Self-healing protective coatings with chitosan based pre-layer reservoir [48], chitosan/diclofenac coatings for medical grade stainless steel [49], copper modified chitosan inhibition of AA-2024 corrosion [50], 2-Mercaptobenzothiazole (MBT) based functionalized chitosan-based coatings for active corrosion protection of AA2024 alloy [51], chitosan/Silver nanoparticles composite on St37 steel corrosion in a 15% HCl solution [52], self-healing protective coatings chitosan doped with cerium nitrate for inhibition of aluminum alloy 2024 [53] and Poly(itaconic acid)-modified chitosan for inhibition of aluminum corrosion [54] and other composites materials have also been investigated as effective chitosan based coatings.…”
Section: Main Bodymentioning
confidence: 99%